Challenges in interdisciplinary weight management in primary care: lessons learned from the 5As Team study. Issue 2 (27th January 2016) - Asselin, J.; Osunlana, A. M.; Ogunleye, A. A.; Sharma, A. M.; Campbell‐Scherer, D.
Summary: Increasingly, research is directed at advancing methods to address obesity management in primary care. In this paper we describe the role of interdisciplinary collaboration, or lack thereof, in patient weight management within 12 teams in a large primary care network in Alberta, Canada. Qualitative data for the present analysis were derived from the 5As Team (5AsT) trial, a mixed‐method randomized control trial of a 6‐month participatory, team‐based educational intervention aimed at improving the quality and quantity of obesity management encounters in primary care practice. Participants ( n  = 29) included in this analysis are healthcare providers supporting chronic disease management in 12 family practice clinics randomized to the intervention arm of the 5AsT trial including mental healthcare workers ( n  = 7), registered dietitians ( n  = 7), registered nurses or nurse practitioners ( n  = 15). Participants were part of a 6‐month intervention consisting of 12 biweekly learning sessions aimed at increasing provider knowledge and confidence in addressing patient weight management. Qualitative methods included interviews, structured field notes and logs. Four common themes of importance in the ability of healthcare providers to address weight with patients within an interdisciplinary care team emerged, (i) Availability; (ii) Referrals; (iii) Role perception and (iv) Messaging. However, we find that what was key to our participants was not that these issues be uniformly agreed upon by all team members, but rather that communication and clinic relationships support their continued negotiation. Our study shows that firm clinic relationships and deliberate communication strategies are the foundation of interdisciplinary care in weight management. Furthermore, there is a clear need for shared messaging concerning obesity and its treatment between members of interdisciplinary teams.